Kaedah Pengajaran dan Pembelajaran Bahasa Melayu - Nazir, Faridah; Alias, Maridah (SYFE Management Sdn Bhd, 2021)
This book focuses on the method of teaching the Malay language in primary school based on the Primary School Standard Curriculum (KSSR). There are 9 chapters that describe the theory of language description, the theory of language acquisition, the application of teaching and learning strategies according to various strategies and approaches. The application of language teaching and learning methods is also fully described with appropriate examples.